Efeito da N-acetilcisteína no déficit cognitivo induzido pela estreptozotocina em camundongo - Costa, Michael Daniel da (2016)
Cognitive impairment is a mental disorder which is associated with neurodegenerative diseases such as Alzheimer's disease (AD), which is the most common form of dementia. Currently there are no consistent evidence who allow support any measure for the prevention of this disease (DAVIGLUS et al., 2010). As for its treatment, there are methods which can provide relative relief of the symptoms, however, only of palliative nature. Thus, this study aimed to evaluate the n-acetylcysteine (NAC), a molecule with neuroprotective properties, in the treatment and prevention of subsequent dementia of AD, using an experimental model of dementia induced by streptozotocin (STZ) in mice. Initially the effect of NAC on the activity of acetylcholinesterase (AChE) activity in vitro mouse brain was evaluated. The ideal dithiobisnitrobenzoate (DTNB) concentration and pH was 0.3 mM and 7.4, respectively. Linearity in enzyme activity was obtained at acetylthiocholine (ATCh) concentrations ranging from 0.025 to 0.450 mM. Sixty sec prior to the addition of ATCh range to avoid interference DTNB NAC interaction was added to the method. NAC interfered with AChE Vmax starting at the concentration of 75 uM without affecting the Km, featuring a non-competitive inhibition. In a second instance, we evaluated the NAC effect on the short-term cognitive impairment in mice. For this, the animals were divided into four groups and were treated with NAC (50 mg/kg /day v.o.) or saline for nine consecutive days, and with STZ (2.5 mg/kg i.c.v.) or aCSF at the first and third days. The results show that NAC treatment: 1) normalized the latency to find the platform in the water maze (MWM) and to get off the platform in passive avoidance (SDPA) that had been altered in animals that received STZ; 2) normalized the AChE and butyrylcholinesterase (BChE) and restored the acetylcholine (ACh) levels in cortical and hippocampal enzymatic activity potentiated by STZ; 3) protected the brain energy metabolism imbalance induced by STZ. Finally, we evaluated the effect of NAC on the long-term cognitive impairment in mice. To this end, animals were treated with NAC (5 mg/kg/day v.o.) or saline for 30 consecutive days, and with STZ (2.5 mg/kg i.c.v.) or aCSF the first and third days. A treatment with physostigmine (PHY; 0.25 mg / kg / day V.O.) was done in parallel as a positive control measure. Totalizing six groups. Both treatments with NAC and PHY: 1) reduced the latency to find the platform in the water maze (MWM) and increased exploratory time on the new object task (NOR) of those animals that received STZ; 2) normalized the cortical and hippocampal AChE enzymatic activity enhanced by STZ; 3) rescued the synaptic plasticity, recovering the synaptophysin (SYN), microtubule-associated protein type 2 (MAP2) and glial fibrillary acidic protein (GFAP) levels reduced by STZ. Thus, the NAC treatment protected from the cognitive impairment induced by STZ in mice, normalizing the cholinergic activity and reestablishing synaptic plasticity.